Epidemiological investigation of porcine Mycoplasma hyopneumoniae in pig herds in Guangxi, China (2022–2023) and genetic diversity analysis based on multilocus sequence typing - Zhou, Ying; Zhao, Shuo; Liang, Longhua; Qin, Yibin; Cheng, Ke; Chen, Zhongwei; Lu, Bingxia; Duan, Qunpeng; Peng, Ying; Huang, Yu; Duan, Zhenhua; Jiang, Kaiyi; et al. (Frontiers in Veterinary Science, 2025)
IntroductionMycoplasma hyopneumoniae (Mhp) infection significantly challenges Guangxi’s pig farms, yet its prevalence and molecular characteristics remain poorly understood. This study aimed to define circulating Mhp genotypes and their distribution in the region.MethodsFrom 2022–2023, 1,362 pig lung samples were randomly collected from 14 Guangxi regions. Mhp was detected using TaqMan Real-time PCR. Strong positive samples underwent multilocus sequence typing (MLST) of adk, rpoB, and tpiA genes to assess genetic relationships.ResultsOf 1,362 samples, 655 (48.1%) were Mhp-positive. MLST amplification succeeded for 61 samples, revealing 27 sequence types (24 novel) across all 14 regions. Phylogenetic analysis indicated predominant circulation of Mhp types I and V. High Mhp incidence and substantial genetic diversity were observed.DiscussionThis study provides comprehensive analysis of Mhp in Guangxi, revealing high prevalence and genetic diversity dominated by types I and V. These findings expand understanding of Mhp epidemiology in China and offer a theoretical foundation for developing prevention and control strategies in Guangxi.